Analysis Ability Literacy Mathematics Reviewed from Self Efficacy Junior High School Students - Nada, Yusrina Qotrun; Yulianto, Alfany Rahman; Iffah, Rona Dhiya Layli (International Journal of Research in Mathematics Education, 2024)
study in study This to explain about ability literacy mathematics participant reviewededucation from self efficacy. Research This aiming for analyze and describe ability literacy mathematicsbased on self efficacy participant educate with category high, medium, and low. Research Thisconducted at PKBM Homeschooling HSPG Purwokerto . Subject study this is participant educate 9thgrade of junior high school. Taking sample use propositional sampling with take subject in accordancewith topics developed. Data collection techniques with use questionnaire, test written, and interviews.While data analysis using analysis qualitative descriptive for describe in detail related ability analysismathematics reviewed from self efficacy. Research results mention that participant educate with selfefficacy tall own ability literacy good mathematics, thing that proven with results workmanshipsystematic questions. While the participantsstudents who have ability self efficacy currently own abilityenough math well, some indicator literacy mathematics can done with good although Still there aresome who haven't maximum. Then the participants educate with self efficacy low own ability literacyvery poor mathematics, thing that proven with less results in every indicator evaluation literacymathematics. Based on results study that self efficacy influence ability literacy mathematics participanteducate, because self efficacy play a role important in build belief participant educate in to his abilityin finish question mathematics .